Advancements in Retrofitting Masonry Structures: A Review on Fiber Reinforced Polymer (FRP) Applications - Musharaf Farooq; Ajay Vikram (Bulletin of Engineering Science, Technology and Industry, 2025)
Retrofitting masonry structures to enhance their structural resilience and seismic resistance is a growing concern in civil engineering. Fiber Reinforced Polymer (FRP) systems have emerged as a promising solution due to their superior mechanical properties, lightweight nature, and adaptability. This review paper synthesizes the latest advancements in FRP applications for masonry retrofitting, emphasizing the research gaps identified in experimental studies. The effectiveness of Carbon Fiber Reinforced Polymer (CFRP), Glass Fiber Reinforced Polymer (GFRP), and Basalt Fiber Reinforced Polymer (BFRP) in tensile, compressive, and seismic performance is critically analyzed. While previous research demonstrates substantial performance improvements, issues such as debonding, anisotropic behavior, and long-term durability remain unresolved. This review underscores the necessity for optimizing installation techniques, hybrid FRP systems, and sustainable material alternatives to enhance the efficiency and applicability of FRP retrofitting in masonry structures.